2020
DOI: 10.21203/rs.3.rs-103392/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shear sensor mechano-signaling determines tendon stiffness and human jumping performance

Abstract: Tendons enable movement by transferring muscle forces to the skeleton, and athletic performances critically rely on mechanically-optimized tendons. How load-bearing structures of tendon sense and adapt to physical demands is an open question of central importance to musculoskeletal medicine and human sports performance. Here, with calcium imaging in tendon explants and primary tendon cells we characterized how tenocytes detect mechanical forces and determined collagen fiber-sliding-induced shear stress as a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…LOX crosslinks are another critical element in providing mechanical strength and transferring load between fibrils [5,6,[70][71][72][73]. It is not well understood how mature LOX crosslinks form [74,75], but it is thought to be due to a cellular response to load [71,76,77]. In this study loading significantly increased LOX activity temporally throughout culture, with 10% load inducing a 2-fold higher activity at 0 and 6 weeks in comparison to 5% load (Fig.…”
Section: Figure 7: Loading Had Little-to-no Effect On Acellular Const...mentioning
confidence: 60%
See 1 more Smart Citation
“…LOX crosslinks are another critical element in providing mechanical strength and transferring load between fibrils [5,6,[70][71][72][73]. It is not well understood how mature LOX crosslinks form [74,75], but it is thought to be due to a cellular response to load [71,76,77]. In this study loading significantly increased LOX activity temporally throughout culture, with 10% load inducing a 2-fold higher activity at 0 and 6 weeks in comparison to 5% load (Fig.…”
Section: Figure 7: Loading Had Little-to-no Effect On Acellular Const...mentioning
confidence: 60%
“…6). It has been previously reported that cyclic loading of mature tendons stimulates or activates the cellular mechanical stretch ion channel PIEZO1 and it has been suggested this activation of PIEZO1 stimulates LOX synthesis, producing stronger tendons [77]. Further, it has been reported PIEZO1 is strain dependent in chondrocytes, with only strains higher than 8% triggering the channel [76,[78][79][80].…”
Section: Figure 7: Loading Had Little-to-no Effect On Acellular Const...mentioning
confidence: 99%
“…However, future development of FE models of Achilles tendinopathy patients will necessitate the incorporation of subject-specific frictional contact, to also take into account the alterations in non-uniform deformation within sub-tendons for estimation of the AT strains. In general, positive AT adaptation is not only dependent on strain magnitude but also time-and rate-dependent (Passini et al, 2021;T. Wang et al, 2015).…”
Section: Limitationsmentioning
confidence: 98%
“…Another gain-of-function mutation in Piezo1 gene, known as E756del has been linked to enhanced athletic performance and the ability of protection against severe malaria. When performing leaping actions requiring high tendon loading, energy storage, and return, carriers of the E756del mutation outperform non-carriers by a large margin (Passini et al, 2021). Recent case reports have highlighted skeletal manifestations associated with Piezo1 mutations, demonstrating the diverse impact of this gene on human health.…”
Section: The Function Of Piezo1mentioning
confidence: 99%